El género y la edad frente a las reconfiguraciones en los medios de subsistencia originadas por la minería en el Perú - Himley, Matthew (2011)
The article investigates the social unevenness of the complex livelihood transformations generated by largescale mining in Peru. Drawing on research undertaken in a caserío located in the area of influence of the Pierina gold mine, I explore the significance of gender and age in shaping how residents have experienced the impacts and opportunities of extraction. In a context in which opportunities to directly benefit from the new mining economy have been available primarily to working-aged men, the evidence suggests that women and older residents have experienced the negative effects of mine construction on their traditional agro-pastoral practices especially acutely. These findings underscore the need to more thoroughly examine the ramifications of mining for the more vulnerable segments of Andean society.